Social Cultural Aspects During Childbirth of Coastal Community Mamuju Regency - Rizky Febriyanti Supriadi; Ashriady Ashriady; Dina Mariana; Ajeng Hayuning Tiyas; Luthfi Agus Salim (Poltekkes Kemenkes Palu, 2025)
Background: Pregnancy and birth experience is essentially a social construction shaped by cultural perceptions and practices. It is crucial for healthcare professionals to identify the most common practices in their environment to improve the concept of care for the patients. This study aimed to determine the socio-cultural aspects of childbirth care in the coastal area of Mamuju (Karampuang and Beru-Beru villages), Mamuju Regency. Methods: This study use a qualitative research method with a phenomenological approach. The subjects of this study consisted of the primary informants, the mothers in labor, and supporting informants, the village midwives, shamans, and community leaders. Results: It showed that the socio-cultural aspects during childbirth were in the form of myths or beliefs related to specific behaviors and rituals. The behavior is a form of symbolic language containing the meaning of merit or to ease the labor process. From a health perspective, these myths do not have a direct negative impact on health status. However, some myths can maintain and improve maternal health if adequately supervised. Conclusion: Healthcare professionals need a synergistically and sustainably practical communication approach to change attitudes and behavior related to childbirth care with an adaptive approach while respecting the good values in every aspect of culture.